Position statement by the Pelvic Floor Society on behalf of the Association of Coloproctology of Great Britain and Ireland on the use of mesh in ventral mesh rectopexy - Mercer‐Jones, M. A. (Colorectal Dis, 2020)
1. Available evidence suggests that mesh morbidity for VMR is far lower than that seen in transvaginal procedures (the main subject of current concern) and lower than that observed following other abdomino‐pelvic procedures for urogenital prolapse, e.g. laparoscopic sacrocolpopexy. 2. VMR should be performed by adequately trained surgeons who work within a multidisciplinary team (MDT) framework. Within this, it is mandatory to discuss all patients considered for surgery at an MDT meeting. 3. Clinical outcomes of surgery and any complications resulting from surgery should be recorded in the TPFS‐hosted national database (registry) available for this purpose; in addition, all patients should be considered for entry into ongoing and planned UK/European randomized studies where this is feasible. 4. A move towards accreditation of UK units performing VMR will improve performance and outcomes in the long term. 5. An enhanced programme of training including staged porcine, cadaveric and preceptorship sessions will ensure the competence of surgeons undertaking VMR. 6. Enhanced consent forms and patient information booklets are being developed, and these will help both surgeons and patients. 7. There is weak observational evidence that technical aspects of the procedure can be optimized to reduce morbidity rates. Suture material choice may contribute towards morbidity. The available evidence is insufficient to support the use of one mesh over another (biologic vs synthetic); however, the use of polyester mesh is associated with increased morbidity.